Preliminary findings on the volatile oil obtained from the fresh leaves of Citron Citrus medica L. (Fam. Rutaceae) - Lubuguin, Antonina Tela; Castillo, Amorita V.; Concepcion, Adoracion B. (Quezon City: Department of Industrial Pharmacy, College of Pharmacy, University of the Philippines, 1978.)
The fresh leaves of Citrus medica L. (Family Rutaceae) common name citron yielded 0.3% v/w of citron oil and a moisture content of 74.5%.
The physical and chemical properties of the oil were determined. Refractive index ranged from 1.4717 to 1.4719. Maximum wavelength was at 212 nm and components limonene and citral were identified. Citron oil is soluble in ether, chloroform, benzene and absolute alcohol and insoluble in acetone and water.
Pure benzene gave three spots using TLC analysis and were compared with limonene standards.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, June 2018.
Keywords: Citrus oils